ISIS Defeat In The Middle East: It's Impact On The Increase Of ISIS Power In The Southeast Asia (Case Study: The Increasing Number Of ISIS Member In Indonesia) - Kibtiah, Tia Mariatul; Yustikaningrum, Richa Vidya (Journal of Strategic and Global Studies, 2018)
This study intended to discover on the increase of number of Islamic States and Syria (ISIS) member in Indonesia. Post ISIS defeat their existence in Middle East, it caused ISIS tried to expand their influenced and began to build other region, such as Southeast Asia as their base of struggle. This article has focused on how to impact the increasing of ISIS in the Philippines to Indonesia, especially is Marawi. We analyzed from border aspect because Marawi is the nearest border with Indonesia’s territory. The existence of ISIS in Indonesia was also inseparable from the strengthening of ISIS in Marawi, Southern Philippines. ISIS in Marawi is challenging to be paralyzed by the Philippine Government. Although President Duterte is going to crush ISIS in Philippine within a year, if Philippines prefer to fight ISIS by itself, without cooperation with another state in South East Asia region, it may lack on the probability of the mission tend to gain success. In fact, ISIS Philippines as a part of a group of which afiliated with the MNLF Movement (Moro National Liberation Front), MILF (Moro Islamic Liberation Front) and Abu Sayyaf. They have bailed out at ISIS after the MNLF made several deals with the government and the Abu Sayyaf suffered a lot. There are some subsections in this paper, first, analyze on ISIS and factors caused the increase the number of ISIS member in Indonesia. Second, in regards the territorial border among Indonesia, Philippines, and Malaysia, we applied terms of cooperative security, to analyze to what extent this states could improve their strategy for strengthening border security to avoid ISIS spread their power in this territory.